Mother’s Self-Efficacy in Caring for Children with Cancer - Hasnani, Fenti (Asian Journal of Pharmaceutical Research and Development, 2022)
Cancer is the main cause of death in children in Indonesia. Childhood cancer is cancer that attacks children under 18 years old, including children who are still in the womb. Mothers play a major role in the process of child development. This study aims to identify the mother’s self-efficacy in the care of children with cancer. This study uses a quantitative descriptive design. Maternal self-efficacy data was collected using a mother’s self-efficacy questionnaire in carrying out treatment for cancer children modified from Bandura’s Theory. The questionnaire used a Likert scale and data collection was carried out from February to July 2022 with 118 respondents who were mothers of children with cancer. The results show that mothers who have high self-efficacy will have high ability or confidence in caring for children with cancer, so they can accompany children in the process of child care, treatment, and healing. The mother’s role is very important in determining the success rate of the treatment process and the survival of children with cancer.